2013
DOI: 10.1016/j.devcel.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Hemogenic Endothelial Cell Specification Requires c-Kit, Notch Signaling, and p27-Mediated Cell-Cycle Control

Abstract: SUMMARY Delineating the mechanism(s) that regulate the specification of hemogenic endothelial cells from primordial endothelium is critical for optimizing their derivation from human stem cells for clinical therapies. We previously determined that retinoic acid (RA) is required for hemogenic specification, as well as cell cycle control, of endothelium during embryogenesis. Herein, we define the molecular signals downstream of RA that regulate hemogenic endothelial cell development, and demonstrate that cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
114
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 46 publications
1
114
1
Order By: Relevance
“…Like HSPC within adult bone marrow 17 , embryonic hemogenic endothelial cells and HSPC exhibit Hoechst dye efflux properties and therefore appear within the "side population" (SP) of cells on a FACS plot 5,11,12 (as shown in Figure 3). In addition, we have also shown that hemogenic endothelial cells express markers of both endothelial and stem cells (Flk1 and cKit, respectively), but do not express the hematopoietic lineage marker, CD45 5,11,12 . Thus, hemogenic endothelial cells can be identified and isolated by FACS as Flk1+/cKit+/CD45-SP cells, and we have shown that these cells give rise to HSPC contained within the Flk1-/cKit+/CD45+ SP fraction of yolk sac and AGM cells 5,11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Like HSPC within adult bone marrow 17 , embryonic hemogenic endothelial cells and HSPC exhibit Hoechst dye efflux properties and therefore appear within the "side population" (SP) of cells on a FACS plot 5,11,12 (as shown in Figure 3). In addition, we have also shown that hemogenic endothelial cells express markers of both endothelial and stem cells (Flk1 and cKit, respectively), but do not express the hematopoietic lineage marker, CD45 5,11,12 . Thus, hemogenic endothelial cells can be identified and isolated by FACS as Flk1+/cKit+/CD45-SP cells, and we have shown that these cells give rise to HSPC contained within the Flk1-/cKit+/CD45+ SP fraction of yolk sac and AGM cells 5,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the eventual development of an approach for large-scale generation of differentiated blood cell types from multi-lineage HSPC -themselves derived from human pluripotent stem cells via a physiologically relevant hemogenic endothelial cell intermediate -would have incredible therapeutic potential for hematologic, oncologic and regenerative medicine. Towards this goal, we have defined the phenotype of hemogenic endothelial cells, on a clonal level, within the murine yolk sac 11 and AGM 12 , two major sites of definitive HSPC production during embryogenesis. Like HSPC within adult bone marrow 17 , embryonic hemogenic endothelial cells and HSPC exhibit Hoechst dye efflux properties and therefore appear within the "side population" (SP) of cells on a FACS plot 5,11,12 (as shown in Figure 3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations